Stratospheric balloon platform for experiments at altitudes up to 40 km - Libonatti, Juan Marco de Jesus; Alves, Mauro Angelo; Martin, Inacio Malmonge (Seven Editora, 2024)
The Earth’s atmosphere at altitudes between 20 and 40 km is relatively understudied due to the challenging access to this atmospheric layer. Airplanes rarely reach these altitudes, and sounding rockets travel too quickly to remain at this altitude for sufficiently long periods. The only effective way to study this atmospheric layer is through stratospheric balloons. This paper describes a system developed by a team of students from the Instituto Tecnológico de Aeronáutica (ITA, Brazil), consisting of a system (telemetry, onboard electronics, and data acquisition and storage subsystems) carried by stratospheric balloons to conduct scientific experiments and also serve as a testing platform for systems and components intended for use in nanosats. A balloon flight using this platform, which carried a Geiger-Müller counter, is also described. DOI:https://doi.org/10.56238/sevened2024.025-019